THE PECULIARITIES OF BOOK SALES SERVICES AND THE OBJECTIVE NEED TO INCREASE THEIR EFFECTIVENESS - Usmanova Nigina Marupovna (Scholar Express Journals, 2023)
The article explores the specifics of bookselling services and the objective need to improve their effectiveness, and theoretical issues of these. It looked at the subjects involved in the formation of the book trade, economic relations between consumers and publications in the book trade, the peculiarities of the book trade. The study also looked at the structural structure of the subjects of the book market and the economic content of their interdependence.
Keywords: Book publishers; libraries; educational institutions